1998
DOI: 10.1002/(sici)1099-0518(19981115)36:15<2707::aid-pola5>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Block copolymers of telechelic poly(phenylene sulfide) and semiaromatic thermotropic liquid crystalline polyester segments

Abstract: We report the synthesis and characterization of copolymers comprising poly(phenyl sulfide) (PPS) blocks and semiaromatic thermotropic liquid crystalline polymer (TLCP) blocks. The copolymers, synthesized by melt‐transesterification of dicarboxy‐terminated poly(phenylene sulfide) with poly(ethylene terephthalate‐co‐oxybenzoate) (PET/OB), were characterized using Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), X‐ray diffraction (XRD), and polarized light optical microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Examples of the first case include blends of PPS modified by diphenylmethane diisocyanate (MDA) and ethylene copolymer elastomer containing maleic anhydride, 8 dicarboxyl-terminated modified PPS and wholly aromatic thermotropic liquid crystalline polymers. 9,10 The second case is a PPS reactive blend with maleic anhydridemodified styrene-ethylene-styrene block copolymer, 11 poly(ethylene-stat-glycidyl methacrylate)-graft-poly(acrylonitrile-stat-styrene), 12 and polyethylene grafted glycidyl methacrylate. 7 Oyama et al found that the size of the phase structure was reduced and the impact strength increased by reactive blending with a series of ethylenegrafted glycidyl methacrylate such as poly(ethylene-ranmethacrylate-ran-glycidyl methacrylate) (EGMA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of the first case include blends of PPS modified by diphenylmethane diisocyanate (MDA) and ethylene copolymer elastomer containing maleic anhydride, 8 dicarboxyl-terminated modified PPS and wholly aromatic thermotropic liquid crystalline polymers. 9,10 The second case is a PPS reactive blend with maleic anhydridemodified styrene-ethylene-styrene block copolymer, 11 poly(ethylene-stat-glycidyl methacrylate)-graft-poly(acrylonitrile-stat-styrene), 12 and polyethylene grafted glycidyl methacrylate. 7 Oyama et al found that the size of the phase structure was reduced and the impact strength increased by reactive blending with a series of ethylenegrafted glycidyl methacrylate such as poly(ethylene-ranmethacrylate-ran-glycidyl methacrylate) (EGMA).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of PPS, there are two possibilities: One in which a reactive functional group is added to the PPS and reactively blended with another polymer; and the other in which a polymer in a reactive functional group is reactively blended with PPS. Examples of the first case include blends of PPS modified by diphenylmethane diisocyanate (MDA) and ethylene copolymer elastomer containing maleic anhydride, 8 dicarboxyl‐terminated modified PPS and wholly aromatic thermotropic liquid crystalline polymers 9,10 . The second case is a PPS reactive blend with maleic anhydride‐modified styrene‐ethylene‐styrene block copolymer, 11 poly(ethylene‐ stat ‐glycidyl methacrylate)‐ graft ‐poly(acrylonitrile‐ stat ‐styrene), 12 and polyethylene grafted glycidyl methacrylate 7 .…”
Section: Introductionmentioning
confidence: 99%